LAS ESCRIBANÍAS MURCIANAS EN LAS REFORMAS DE LOS BORBONES - Montojo Montojo, Vicente (Documenta & Instrumenta - Documenta et Instrumenta, 2008)
The objective of this text is present the analysis historicinstitutional and archivistic of some specials notaries offices, in particular financials and militaries, like those of Service Corps, War and Royal Navy of Cartagena and Murcia, in the 18th century, with their precedings of the notary offices of the fleets and frontiers’s Appointment of Cartagena, and of Governor and War of reign of Murcia, in the 17th century, and their documentary production. The origin of these clerk’s offices (the notary’s offices of War and Royal Navy) is an indication of an interesting relation into militaries archives (the Naval Archive of Cartagena, old Historic Archive of the Navy in Cartagena and General Archive of the Mediterranean Maritime Zone) and civilest archives: the fundament of the our study is the notary office’s found of the Archivo Histórico Provincial de Murcia. Principally the text falls most heavily in the documentaries groups which produced the institutions of these militaries notaries offices, like there are their expedients, registries and testimonies of autos, in their archivist localization and in their valour like information’s sources for the investigation.